2012
DOI: 10.1089/hyb.2012.0034
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal and Polyclonal Antibodies Specific for Foot and Mouth Disease Virus Type A and Type O VP1

Abstract: The foot and mouth disease virus (FMDV) is an RNA virus composed of single stranded positive sense RNA. FMDV has been known to infect cloven-hoofed animals, including pigs, cattle, and sheep. FMDV is rapidly spreading outward to neighboring regions, often leading to a high mortality rate. Thus, early diagnosis of FMDV is critical to suppress propagation of FMDV and minimize economic losses. In this study, we report the generation and characterization of polyclonal and six monoclonal antibodies against VP1 thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…DAPI staining indicated that VP1 was mainly located in the cytoplasm of the infected cells ( Fig. 1A ), although some VP1 were detected in the nucleus, which is consistent with a previous report on the VP1 protein of FMDV [ 22 ]. The neutralizing activity of mAb 2D10 was then determined by use of an in vitro neutralization assay on DEF cells; mAb 2D10 neutralized the DHAV-1 HP1 virus with a neutralization titer (NT 50 ) of 40.…”
Section: Resultssupporting
confidence: 92%
“…DAPI staining indicated that VP1 was mainly located in the cytoplasm of the infected cells ( Fig. 1A ), although some VP1 were detected in the nucleus, which is consistent with a previous report on the VP1 protein of FMDV [ 22 ]. The neutralizing activity of mAb 2D10 was then determined by use of an in vitro neutralization assay on DEF cells; mAb 2D10 neutralized the DHAV-1 HP1 virus with a neutralization titer (NT 50 ) of 40.…”
Section: Resultssupporting
confidence: 92%
“…In response to a need for additional laboratory reagents to support the study of FMDV, new antibodies recognizing the NS protein 3AB (Lin et al., ), and VP1 of type A and type O (Cho et al., ) have recently been characterized. Furthermore, scientists at PIADC have developed a quantitative colorimetric bioassay to measure the anti‐FMDV activity of bovine and porcine type I IFNs (Ramanathan et al., ).…”
Section: Molecular Biologymentioning
confidence: 99%
“…The expression of the med28 protein was induced by 0.1 mM IPTG at 30°C for 4 h. Protein purification method has been described previously. (11) The cells were harvested, resuspended in 1X PBS, and then lysed by ultrasonication. After centrifugation of the lysate at 8000 g, the pellet was recovered and further solubilized using 1X PBS containing 6 M guanidine-HCl.…”
Section: Generation Of Recombinant Med28 Proteinmentioning
confidence: 99%
“…Methods were followed as described previously. (11) To generate mouse monoclonal antibody, female BALB/C mice (13 weeks old) were immunized subcutaneously. The emulsion was produced by complete mixing of med28 protein (200 mg/200 mL) with equal volume of complete Freund adjuvant (Sigma-Aldrich, St. Louis, MO).…”
Section: Generation Of Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation